Hubungan Kebugaran Fisik dengan Fungsi Kognitif pada Mahasiswi Penghafal Al-Qur'an di Kota Malang: HUBUNGAN TINGKAT KEBUGARAN FISIK DENGAN FUNGSI KOGNITIF PADA MAHASISWI PENGHAFAL AL-QUR’AN DI PONDOK PESANTREN KOTA MALANG - Faradhiza Aini Putri Nasir Nasir; Ali Multazam; Nurul Aini Rahmawati (Jurnal Kesehatan Hesti Wira Sakti, 2024)
Introduction: College students need sufficient physical fitness to be able to think and use their cognitive abilities to the fullest so that they do not get tired quickly after doing busy activities such as lectures and memorizing the Qur’an. These activities also require thinking skills related to cognitive function. Good physical fitness will increase Brain-Derived Neutrophic Fcator (BDNF) protein levels which function to stimulate brain nerve cells to improve cognitive abilities. The research aims to understand the relationship between the level of physical fitness and the cognitive function of female student at the Nurul Furqon Islamic Boarding School, Malang City as a memorizer of the Al-qur’an. Methods: The research will use an observational analytical approach with a cross-sectional study, as many as 30 respondents were obtained using a purposive sampling technique. Data were taken using the YMCA Step Test and MoCA-Ina (Montreal Cognitive Function). Next, data processing uses the Fisher's Exact Test method. Results: The results of the statistical test produce a p value of 0.029 < 0.05. Conclusion: There is a relationship between the level of physical fitness with cognitive function in students who memorize the Qur’an in Malang City.